PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (STUDI PADA KONSUMEN KOSMETIK WARDAH DI KOTA SEMARANG) - Rachmi Murti, Canta Lalita; Ngatno, Ngatno (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2020)
Wardah as one of the leading cosmetic producers in the homeland need to maintain the loyalty of its customers to be able to stay in the middle of strict cosmetic competition. Demands of good cosmetic needs at affordable prices, making the producers who are engaged in the field of cosmetics are continuously innovating to produce products at affordable prices but the quality is well assured. The price is a significant determinant in the cosmetic industry to keep consumers using Wardah products. With good product quality, consumers will survive on a product if the quality of products offered in accordance with consumer expectations. Customer loyalty is a form of customer loyalty to continue using products originating from the same company. Wardah as one of the leading cosmetic producers in the homeland needs to keep its customers loyalty to continue to survive amid intense competition. This research aims to know the effect of price (X1) and product quality (X2) on loyalty (Y) through customer satisfaction (Z) cosmetic user Wardah in Semarang city. This type of research uses explanatory research with data collection techniques through interviews and data collection tools using questionnaires. The data sources in this study are primary data and secondary data. Sampling techniques in this study used purposive sampling and non probability sampling. The sample in this study amounted to 100 respondents in the city of Semarang. Technical analysis uses simple linear regression, multiple linear regression, T-Test, and F-Test with SPSS version 21.00. The results of the analysis with SPSS 21.0Â explained that the results of the direct influence test on the research model showed positive and significant results. The indirect effect test on the research model also showed positive and significant results. Based on the research, researchers suggest that Wardah is more listening to the user's voice about the quality of its products, where users complain about the quality of products that are deemed to be less appropriate to the expectations of the user. While the price is considered to be in accordance with Wardah cosmetic products